Luscious Lanta / Aida Khalida Mohamed Idris ... [et al.] - Mohamed Idris, Aida Khalida; Sulaiman, Suria; Abdullah, Hasniza; Faat, Farhan (Faculty of Hotel & Tourism Management, UiTM Pulau Pinang, 2023)
At the end of May 2025, my family had the chance of travelling to the neighbouring country up north, Thailand. It was an impromptu decision and we just packed up our bags and off we went. We travelled by car where the journey from Penang to the Immigration, Customs, Quarantine and Security (ICQS) checkpoint in Bukit Kayu Hitam took us less than three hours. At Sadao Customs and Immigration checkpoint, we were required to produce these forms before entering the Kingdom of Thailand. The forms needed are: Oriqinal Car Reqistration Card (Grant), Thailand Insurance Form, Information on Conveyance Forms (Inbound and Outbound), Passport, Malaysian Driving License. For forms no 2 and 5, we can acquire these forms from the Sadao Immigration Complex, or we can get them done by tour companies located at roadside in Changloon, Kedah. Normally, these tour companies also sell Thai SIM cards and money exchange services. As we travelled at night upon reaching Dannok, we had our dinner of the famous 'Daging Bakar' and 'Pulut Ayam' yums! We then continued our journey to Hatyai where we spent the night there. The best thing about Thailand is that the hotel's rate is so affordable (cheap!). Why do I say that is because the hotel that we checked into was only TBH 600 per night. As when this article is being written, the exchange rate is TFIB100 = RM 15.25.